Penerapan Model Addie dalam Pembuatan Video Media Pembelajaran tentang Pembangkit Listrik Tenaga Diesel (PLTD) - Norma Suci Pratiwi; Dede Saptudi; Azhar Mahdi; M. Luthfi Fauzi; Fakhri Ismail Haniya; Didik Aribowo (Prosiding Seminar Nasional Ilmu Pendidikan, 2026)
Advances in digital technology have had a positive impact on the development of learning media, particularly the use of video as a means of delivering material. The complexity of Diesel Power Plants (PLTD) requires media that can explain concepts and working processes more clearly. This study aims to develop an instructional video about PLTD using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research method used is Research and Development (R&D). The development process begins with needs and material analysis, followed by storyboard design, video production, implementation through presentation to the audience, and evaluation based on feedback received. The development results indicate that the resulting instructional video presents PLTD material systematically, engagingly, and easily understood by students. The integration of visual, audio, and text elements in the video helps enhance understanding of technical material. Therefore, the instructional video developed using the ADDIE model can be used as an effective learning medium for explaining the concepts and workings of PLTD.